A Framework for Housing Policy Reform in Urban Areas in Egypt : Developing a Well Functioning Housing System and Strengthening the National Housing Program - World Bank (Washington, DC, 2012)
This document builds upon several recent studies and reports carried out in the 2006-2007 period. The first note, entitled analysis of housing supply mechanisms (World Bank), analyzes the situation of housing supply in urban areas in Egypt, including the study of existing formal and informal mechanisms for the delivery of urban housing, the institutions responsible for supply and regulation, the characteristics of the formal and informal stock, and the institutional and regulatory framework governing land use planning and development. The second is a housing demand study in Greater Cairo (USAID TAPRII), which uses household data surveyed in December 2006 and yields results on the housing demand and household characteristics in the Greater Cairo Region. The third is an analysis of subsidized housing programs (USAID TAPRII), which assesses past, existing and pipeline subsidy programs in Egypt. International Best Practices were presented at a high-level workshop held in April 2007 with the intent of assessing different schemes of housing subsidies and reforms used in other emerging markets, in order draw lessons pertinent for Egypt. Finally, a note (World Bank) summarized the framework for moving from a program-based to a policy-based approach to housing sector reform, which was jointly developed by the World Bank and USAID TAPRII teams and discussed with Government of Egypt (GOE) policymakers in the high-level workshops of April and May 2007, and endorsed in September 2007. These studies and reports are briefly summarized in the annex (section seven) to this report.